The Influence of Minangkabau Indigenous Values on Entrepreneurial Orientation and Business Performance in Padang, Indonesia - Mukti Diapepin; Donna Ikranova Febrina (Enigma in Cultural, 2024)
This study investigates the relationship between Minangkabau indigenous values, entrepreneurial orientation (EO), and business performance among entrepreneurs in Padang, Indonesia. Minangkabau culture, with its matrilineal system and emphasis on community and entrepreneurship, provides a unique context to explore how cultural values influence business practices. A quantitative survey was conducted with 300 entrepreneurs in Padang, measuring their adherence to Minangkabau values, EO dimensions (innovativeness, proactiveness, and risk-taking), and business performance (financial and non-financial). Data were analyzed using structural equation modeling (SEM). The findings reveal that Minangkabau values significantly influence EO, with a strong positive relationship between these values and the dimensions of innovativeness and proactiveness. Furthermore, EO was found to be a significant predictor of both financial and non-financial business performance. In conclusion, this study highlights the importance of cultural values in shaping entrepreneurial behavior and business success. The findings suggest that Minangkabau values foster an entrepreneurial spirit that drives business performance in Padang. This research contributes to the understanding of culture's role in entrepreneurship and provides valuable insights for entrepreneurs, policymakers, and researchers in Indonesia and other culturally rich contexts.